International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
The fifth volume of the proceedings of the International Conference on Transportation and Development 2022, held in Seattle, Washington, May 31-June 3, 2022. This collection contains 28 peer-reviewed papers on pavement construction and maintenance. Topics include: performance modeling; hot mix asphalt pavement; maintenance and rehabilitation techniques; cement pavement; and monitoring techniques for pavement conditions.